Prevalence of vitamin D deficiency among medical students in central India: a cross-sectional study - Namrata Dubey; Ankita Mishra (International Journal Of Community Medicine And Public Health, 2026)
Background: Vitamin D deficiency is widely prevalent in India despite adequate sunlight availability. Young adults, particularly medical students with predominantly indoor academic schedules, may be at increased risk of inadequate vitamin D status. However, data regarding vitamin D status among healthy young adults from Central India remain limited. Methods: A cross-sectional observational study was conducted at Central India Medical College, between May 2024 and June 2025. A total of 152 apparently healthy first-year MBBS students aged 17–23 years were enrolled. Demographic characteristics, dietary habits, educational status of the head of the family, socioeconomic status and monthly family income were recorded. Serum 25-hydroxyvitamin D (25(OH)D) levels were estimated using chemiluminescent immunoassay (CLIA) and classified as deficient (